Crisis de la profesión periodística: un abordaje desde el análisis la teoría crítica de la comunicación - Landin Bravo, Carlos Alberto (Machala, 2020)
This research work analyses the crisis of the journalistic profession: an approach based on the analysis of the critical theory of communication, which helps to interpret through research, what type of journalism and journalists currently exist in the province. It fulfills the objective of analyzing the crisis of the journalistic profession in the province of El Oro, based on the postulates of the critical theory of communication. The following objective of analysis helped to fulfill the purpose and sense of the investigation. This analysis was carried out through the qualitative methodology, a method that helped to identify the appropriate investigation technique. The interview with specialists, in which fifteen journalists from different media and institutions were interviewed, was a clear example of this. In addition, it is linked to the contributions of Buitrón and Zavala, which are used in conclusions. In the conclusions, the critical analysis of the journalistic profession in the province is highlighted, being linked to the postulates of the critical theory of communication, the identification of the postulates of the theory transferred to the study, for this purpose the contributions of the interviewees are implemented and the interpretation of the text of Buitrón with the principles of the critical theory and the concept of the journalistic crisis from the thoughts of the journalists, it is worth emphasizing that this text highlights the derogatory action of the journalists in front of economic and status offers offered by the political power.
El presente trabajo de investigación analiza la crisis de la profesión periodística: un abordaje desde el análisis de la teoría crítica de la comunicación, el cual ayuda a interpretar mediante la investigación, cuál es el tipo de periodismo y periodistas que actualmente tiene la provincia. Se cumple con el objetivo de analizar la crisis de la profesión periodística en la provincia de El Oro, a partir de los postulados de la teoría crítica de la comunicación. El siguiente objetivo de análisis ayudó a cumplir con el fin y el sentido de la investigación. Este análisis se lo realizó a través de la metodología cualitativa, método que ayudó a identificar la técnica de investigación adecuada, quedando en evidencia la entrevista a especialistas en la que constan quince periodistas de distintos medios e institucionales. Además de ello se la vincula con las aportaciones de Buitrón y Zavala, mismas que son utilizadas en conclusiones. En las conclusiones se destaca el análisis crítico de la profesión periodística en la provincia, siendo vinculados con los postulados de la teoría crítica de la comunicación, la identificación de los postulados de la teoría transferidos al estudio, para ello se implementan las aportaciones de los entrevistados y la interpretación del texto de Buitrón con los principios de la teoría crítica y el concepto de la crisis periodística a partir de los pensamientos de los periodistas, cabe recalcar que dicho texto resalta el accionar despectivo de los periodistas ante ofertas económicas y de estatus ofrecidos por el poder político.
Keywords: CRISIS PERIODISTICA; ETICA PERIODISTICA; TEORIA CRITICA